"Sususaya” in Research Methodology: A Form of Internalization of Multiparadigms in Accounting Research - Eliza Noviriani (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
This study internalized multiparadigm accounting research using dialogic learning methods to create "new accounting" thinking. Dialogic learning in research methodology courses to explore students' imagination, cognitive dissonance, and critical thinking. Student awareness that the accounting research paradigm is not just on one form. Students realize that data must be presented in any research, regardless of the paradigm used. Students succeeded in sparking a "new accounting" research idea that had not been carried out in the past. This article provides an alternative method of dialogical learning in research methodology courses. Through the dialogical learning method, the internalization of the accounting research paradigm can awaken the imagination, cognitive dissonance, and critical thinking of students to produce a "new accounting" concept.